2017
DOI: 10.1002/2016ja023512
|View full text |Cite
|
Sign up to set email alerts
|

The MAVEN EUVM model of solar spectral irradiance variability at Mars: Algorithms and results

Abstract: Solar extreme ultraviolet (EUV) radiation is a primary energy input to the Mars atmosphere, causing ionization and driving photochemical processes above approximately 100 km. Because solar EUV radiation varies with wavelength and time, measurements must be spectrally resolved to accurately quantify its impact on the Mars atmosphere. The Mars Atmosphere and Volatile EvolutioN (MAVEN) EUV Monitor (EUVM) measures solar EUV irradiance incident on the Mars atmosphere in three bands. These three bands drive a spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 140 publications
(184 citation statements)
references
References 51 publications
4
180
0
Order By: Relevance
“…The echelle observations shown here were made during the declining activity phase of Solar Cycle 24, when the Sun was less active at its maximum than in previous cycles. The solar Lyman α flux at Mars, measured by the MAVEN Extreme Ultraviolet Monitor (EUVM) instrument Lyman α channel (Eparvier et al, ), decreased by ~25%, during the mission observations shown here, when compared with consecutive times in Mars's orbit at similar L s (Thiemann et al, ).…”
Section: Resultsmentioning
confidence: 72%
“…The echelle observations shown here were made during the declining activity phase of Solar Cycle 24, when the Sun was less active at its maximum than in previous cycles. The solar Lyman α flux at Mars, measured by the MAVEN Extreme Ultraviolet Monitor (EUVM) instrument Lyman α channel (Eparvier et al, ), decreased by ~25%, during the mission observations shown here, when compared with consecutive times in Mars's orbit at similar L s (Thiemann et al, ).…”
Section: Resultsmentioning
confidence: 72%
“…The given flare classification is the magnitude irradiance increase in the NOAA GOES X-Ray Sensor (XRS) channel B instrument [Bornmann et al, 1996[Bornmann et al, , 1996. For the cases when the flare was only observed by MAVEN, a scaling is used that converts EUVM-B irradiance measurements to GOES XRS-B values that are determined from a set of flares when both instruments made simultaneous observations (Thiemann et al, 2017 ). Similarly, the reported flare peak time is the peak of the GOES XRS-B, when available, or the peak of the EUVM-B measurements.…”
Section: Overview Of the Mission-long Observationsmentioning
confidence: 99%
“…Such a comprehensive set of observations at Mars will allow the better characterization of the local EUV and solar wind conditions during active space weather periods and analysis of the response of the Martian system to the upstream disturbances. Some of the Mars-impacting space weather events observed by MAVEN include the heating of the neutral atmosphere triggered by large flares [Thiemann et al, 2017], the perturbation of the Martian system and ion escape enhancements due to the passage and interaction of an interplanetary coronal mass ejection (ICME) , and the triggering of diffuse auroral emission in the lower Martian atmosphere due to the precipitation of electrons during a SEP event [Schneider et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…From a preliminary examination of hundreds of orbits, Xu et al (2017) found that such nightside precipitations of photoelectrons are quite common. A convolution of a typical solar moderate EUV spectrum measured by the MAVEN Extreme Ultraviolet Monitor (Eparvier et al, 2015;Thiemann et al, 2017) with the transmission rate at the various wavelengths between 10 and 89 nm has been made, 89 nm being the longest wavelength which can still ionize CO 2 . Temperature-independent photoabsorption cross sections for N 2 , CO, Ar, and O were taken from the PHIDRATES database (https://phidrates.space.…”
Section: 1029/2018ja026336mentioning
confidence: 99%